Disparities in Index of Care for Otolaryngologic Procedures Performed in Ambulatory and Inpatient Settings. (1st March 2022) - Gadkaree, Shekhar K.; McCarty, Justin C.; Sajjadi, Autefeh; Dresner, Harley S.; Lindsay, Robin W.; Varvares, Mark A.; Friedlander, David F.; Bergmark, Regan W.
Abstract : Objective: To compare the same surgical procedure performed in ambulatory and inpatient settings to determine the demographics associated with this selection, the differences in 30‐day revisit rates, and the total 30‐day cost of care. Study Design: Retrospective cohort analysis. Setting: Ambulatory and inpatient centers in Florida, New York, and Maryland. Methods: The Healthcare Cost and Utilization Project, the State Ambulatory Surgery and Services Database, and the State Inpatient Database were used to identify patients undergoing commonly performed otolaryngologic procedures in 2016. The State Emergency Department Database and State Inpatient Database were used to identify 30‐day revisits. Results: A total of 55, 311 patients underwent an otolaryngologic procedure: 51, 136 (92.4%) ambulatory and 4175 (7.6%) inpatient. Adjusted odds of receiving care in the ambulatory setting was significantly lower for Black patients (odds ratio, 0.69 [95% CI, 0.55‐0.85]; P =. 001) and nonspecified other races (odds ratio, 0.71 [95% CI, 0.52‐0.95]; P =. 001) as compared with White patients. Women had 1.16‐higher adjusted odds of undergoing a procedure in the ambulatory setting (95% CI, 1.05‐1.29; P =. 005). Insurance status and income were associated with location of care in the subcategorization of head and neck surgery. Adjusted inpatient procedure costs were significantly more than ambulatory (median, 59, 112 vs 14, 899); 30‐day adjusted costs were 71, 333.07 (95% CI, 56, 223.99‐86, 42.15; P <. 001) more expensive for inpatient procedures vs ambulatory; and the adjusted 30‐day odds of revisit were 2.23 times greater (95% CI, 1.44‐3.44; P <. 001) for ambulatory surgery across all procedures. Conclusions: Disparities exist in the use of ambulatory settings to provide otolaryngologic surgery. Additional research is required to ensure equitable triaging of surgical care setting.